Analysis of Unsecured Loans (KTA) in terms of the Prudential Banking Principle - Noer Dini Camelia; Rifkah Romizah; Iftitah Dian Ukhrowi; Ihsyan Jani Syamsi (IHSA Institute, 2022)
Bank is an intermediary institution that accommodates public funds and distributes them in the form of credit. One of the credit loan facilities provided by banks is Unsecured Loans (KTA). The existence of Unsecured Credit (KTA) causes banks to be deemed not to carry out their obligations to apply one of the principles in banking, namely the Prudential Principle as contained in the provisions of Article 8 of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking. Unsecured Credit (KTA) is a form of bank facility that is considered very risky because it does not meet the credit principles that are guaranteed by banks in providing loans, known as the